2022
DOI: 10.3390/su14031298
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Urban Complexity via the Spatial Diversity of Activities: An Application to Barcelona (Spain)

Abstract: Urban complexity can be measured by the numerical and spatial diversity of activities in a territory. Just as biodiversity can be measured in a natural ecosystem, diversity indices can be applied to urban settings. Urban diversity presents higher values in areas where there is a greater number of (economic, institutional, and social) activities with a high degree of differentiation between them. This study seeks to investigate the potential of applying an urban diversity index in a specific case study: namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…As Rueda Palenzuela et al. (2022) observed in a study of Barcelona, the lowest urban diversity values are normally found in the peripheral areas of the city (Figure 10a2,c3), while the highest diversity is in the city center (Figure 10a1,a3). In other words, isolated and edge‐type growth normally show low diversity, while infilling growth triggers higher diversity.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…As Rueda Palenzuela et al. (2022) observed in a study of Barcelona, the lowest urban diversity values are normally found in the peripheral areas of the city (Figure 10a2,c3), while the highest diversity is in the city center (Figure 10a1,a3). In other words, isolated and edge‐type growth normally show low diversity, while infilling growth triggers higher diversity.…”
Section: Resultsmentioning
confidence: 58%
“…Both concepts are particularly important in Spain, where the policies adopted to comply with the Urban Agenda for the EU and the UN 2030 Agenda have focused their efforts on sustainable urban development through the pursuit of urban diversity and efficient management of urban expansion, among other aspects. As a result, both the creation of a diverse urban environment (Rueda Palenzuela et al, 2022) and the control of urban sprawl (Díaz-Pacheco & García-Palomares, 2014) have become important topics on the spatial planning agenda in Spain. However, most existing studies have focused on the analysis and description of past urban growth processes, rather than analyzing possible future scenarios such as those derived from vector urban land simulation maps (Molinero-Parejo et al, 2023), which can assist in the design of proactive policy packages adapted to these scenarios (Ariza-Álvarez et al, 2023).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation model used here is part of the operational research tools within the multidimensional analysis referred to by the tools that support shared decision-making processes, extending the knowledge of the utility sphere to the value sphere [48]. The first concerns mainly functional aspects, and the second also includes variables that refer more or less directly to ethical and aesthetic values [49].…”
Section: The Mavt-based Modelmentioning
confidence: 99%
“…Hence, implementation plans were tailored to each neighbourhood and agreed upon as a result of a protocol and a road map for organizing the participation of stakeholders through joint commissions and regular meetings (Ajuntament de Barcelona, 2020b). The initial Superblocks plan has since transitioned to the development of green axes (see differences between the alternatives superB_*** and eixV_***) (Ajuntament de Barcelona, 2021b), but the effectiveness of this approach to address the societal and environmental challenges of the city has been questioned (Rueda Palenzuela, 2022;Suñé, 2022).…”
Section: Policy-makingmentioning
confidence: 99%